2019
DOI: 10.1139/apnm-2018-0293
|View full text |Cite
|
Sign up to set email alerts
|

Are French Canadians able to accurately self-rate the quality of their diet? Insights from the PREDISE study

Abstract: The main objective of this study was to compare self-rated diet quality to a more comprehensive score of diet quality and to assess the ability of self-rated diet quality to predict adherence to healthy eating guidelines. This study also aimed at evaluating the influence of individual characteristics on the association between self-rated diet quality and the overall diet quality score. As part of the PREDISE study, 1045 participants (51% women) from the Province of Québec, Canada, self-rated their diet quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
(43 reference statements)
2
3
0
Order By: Relevance
“…A similar conclusion was reached by Canadian researchers who suggested that a single item self-rated DQ measure should be used with caution due to its poor ability to predict adherence to healthy eating guidelines. 22 The high percentage of adults found in the present study who overrated their DQ (84%) supports results reported in a study of US adult cancer survivors in which 56% overrated their DQ. 10 In the present study, only one-fourth of adults reported being aware of MyPlate and less than 10% reported trying to follow MyPlate dietary recommendations.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…A similar conclusion was reached by Canadian researchers who suggested that a single item self-rated DQ measure should be used with caution due to its poor ability to predict adherence to healthy eating guidelines. 22 The high percentage of adults found in the present study who overrated their DQ (84%) supports results reported in a study of US adult cancer survivors in which 56% overrated their DQ. 10 In the present study, only one-fourth of adults reported being aware of MyPlate and less than 10% reported trying to follow MyPlate dietary recommendations.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to the current study, studies conducted with French-Canadian adults and US household meal planners/preparers found that women’s DQ ratings were more accurate than men’s ratings. 22,23 Also similar to the current study, cancer survivors with lower income and lower educational attainment were more likely to accurately assess their DQ. 10 Dissimilar from the current study, no associations between accurately assessing DQ and race/ethnicity and perceived weight status were found among US household meal planners/preparers and less than a high school education was associated with lower odds of accurate assessment.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This study was conducted with data from a large cross-sectional research project (PRÉDicteurs Individuels, Sociaux et Environnementaux (PREDISE) study) aiming to identify determinants of healthy eating in a probabilistic sample of French-speaking adults from the Province of Québec. Details about recruitment and collected measures are presented elsewhere [23,24]. Briefly, this multicenter web-based study was designed to examine how individual, social, and environmental factors are associated with the adherence to Canadian dietary guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were recruited as part of the PREDISE (PRÉDicteurs Individuels, Sociaux et Environnementaux) study, a multicentre cross-sectional study aimed at identifying determinants of the adherence to dietary guidelines among French-speaking adults from the Province of Québec, Canada. Recruitment and procedures were described previously [39]. Briefly, a probability sample of French-speaking men and women from the Province of Québec aged 18 to 65 were included in the study.…”
Section: Participants and Proceduresmentioning
confidence: 99%